Wafer‐Scale InN/In2S3 Core–Shell Nanorod Array for Ultrafast Self‐Powered Photodetection. (16th December 2021) - Cao, Ben; Liu, Qianhu; Zheng, Yulin; Tang, Xin; Chai, Jixing; Ma, Shufang; Wang, Wenliang; Li, Guoqiang
Abstract: Self‐powered photodetectors have paved the way for electronic applications in fields such as civilian communication, infrared mapping, and industrial automatic control. However, most self‐powered photodetectors have faced photoresponse‐speed and device‐scale bottlenecks. Herein, a novel, self‐powered detector with an ultrafast response speed based on a core–shell InN/In2 S3 nanorod array is proposed. A wafer‐scale InN/In2 S3 nanorod array with good homogeneity is synthesized on Si substrates via a simple two‐step method involving molecular beam epitaxy and chemical vapor deposition. The photodetector device exhibits excellent self‐powered properties and a high current on/off ratio of 5 × 10 3 . Further analyses determined that the device have an excellent photovoltaic responsivity and detectivity of 140 mA·W −1 and 4.0 × 10 10 Jones, respectively (0 V). Impressively, the device exhibits an ultrafast photoresponse with a rise/fall time of 22/32 µs. The self‐powered InN/In2 S3 photodetector with an ultrafast response speed shows superior potential for electronic applications. The core–shell nanostructure hybrid heterojunction introduces a novel idea for wafer‐scale nano‐photodetectors. Abstract : A wafer‐scale InN/In2 S3 nanorod array with good homogeneity is grown on Si substrates for ultrafast photodetection. Following analysis of the synthesis mechanism of the In2 S3 /InN/Si heterojunction, the photodetector device exhibits excellent self‐powered properties and an ultrafast photoresponse with a rise/fall time of 22/32 µs. The core–shell nanostructure hybrid‐heterojunction introduces a novel idea for wafer‐scale nano‐photodetectors.